Voluntary International Financial Reporting Standards Application: A Bibliometric Review and Future Research Directions - Ngoc Giau Nguyen; Ngoc Tien Nguyen (International Journal of Financial Studies, 2025)
This study aims to review research on voluntary IFRS application and future research directions. This study presents a bibliometric review of 185 studies on voluntary IFRS application using Web of Science data and R software. Four research clusters are identified: (i) determinants of IFRS voluntary application, (ii) corporate disclosure, (iii) voluntary disclosure, and (iv) economic consequences, with detailed analysis and future research question extraction. These research clusters enable us to extract future research questions, highlighting the avenues where further investigation is needed. This study provides practical insights for policymakers and practitioners. Researchers can leverage our work to grasp the current state of knowledge, identifying active and impactful research areas. This guidance can inform their investigations, though this study relies solely on data from the Web of Science database. This study provides a comprehensive overview of the existing literature on voluntary IFRS application, helping researchers, practitioners, and policymakers understand the current state of research in this field.